Sensory Stimulating Sanctuaries - Creating spaces that improve and benefit wellbeing and mental health through sensory stimulating architectural techniques - Relling, Hermien (School of Architecture, Planning and Geomatics, 2023)
The rise of the ‘modern-day illnesses' such as anxiety, mental health struggles and issues relating to posttraumatic stress, influence people on a daily basis. I wonder how architectural techniques could be used to stimulate one's senses so as to allow for a calming feeling or create a sense of well-being and safety within a space. In this paper I complete an in-depth study that focusses on ways in which architecture could be used to benefit one's mental health by implementing trauma informed design techniques. I draw on trauma-informed design theories, phenomenology as a philosophy, as discussed by Husserl, as well as its connection with architecture by referencing the work of Juhani Pallasmaa and Peter Zumthor. Therapeutic landscapes, as well as the theory of colour and biophilia help to identify the necessary spatial and material qualities that contribute to the favourable design of wellness centres. The understanding of these studies lead to a set of design principles, as described by Christopher Alexander, that act as guide lines for the successful design of a trauma-informed healing sanctuary, rather than the institutional approach. The sensory stimulating sanctuary is located on the Upper Campus of the University of Cape Town and prioritises the mental health of students attending tertiary institutions. The site allows for a biophillic design, as the strong relationship with nature is a noticeable feature. The structural and interior design elements of the design project prioritises a trauma-informed approach and finds the balance between sanctuary and institution to result in an efficient, yet inviting, healing space.